Examining the utility of a decision-support tool to develop spatial management options for the protection of vulnerable marine ecosystems on the high seas around New Zealand. (15th March 2019) - Rowden, A.A.; Stephenson, F.; Clark, M.R.; Anderson, O.F.; Guinotte, J.M.; Baird, S.J.; Roux, M.-J.; Wadhwa, S.; Cryer, M.; Lundquist, C.J.
Abstract: The South Pacific Regional Fisheries Management Organisation (SPRFMO) Convention includes specific provisions to protect vulnerable marine ecosystems (VMEs). The SPRFMO Commission has determined that the interim measures put in place to protect VMEs should be replaced by an improved system of fishable and closed areas. We used the conservation planning tool Zonation to examine the utility of a decision-support tool to develop spatial management options that balance the protection of VMEs with utilisation of high value areas for fishing. Input data included: habitat suitability maps for VME indicator taxa, and uncertainties associated with these model predictions, for an area of the high seas around New Zealand; naturalness condition, represented by two proxy variables using New Zealand trawl effort data; and value to the New Zealand fishery using trawl catch data for two gear types and three time-periods. Running scenario analyses with these data allowed for an understanding of the effect of varying the input data on the spatial prioritisation of areas for VME conservation. The analyses also allowed for the cost to fishing to be determined, in terms of the amount of the trawl catch footprint (normalised to the catch) lost if high priority areas for VME indicator taxa are protected. In most scenarios, the cost to fishing was low given the relatively high proportion of suitable habitat for VME indicator taxa that could be protected. The main outcome of the present study is a demonstration of the practical utility of using available data, including modelled data, and the Zonation decision-support tool to develop future options for the spatial management of the SPRFMO area. Suggestions are also made for improvements in input data for future analyses. Highlights: A decision-support tool was assessed for identifying spatial conservation priorities. Spatial conservation prioritisation is sensitive to varying the input data. Balancing the protection of VMEs and use of high value fishing areas is possible. Cost to fishing was low given amount of VME habitat that could be protected. Use of a decision-support tool can improve current spatial management measures.